Sources of Mistrust: An Experimental Case Study of a Central Asian Water Conflict - Abbink, Klaus (2012)
With the disintegration of the USSR a conflict arose between Kyrgyzstan, Uzbekistan and Kazakhstan over the transboundary Syr Darya river. Upstream Kyrgyzstan controls the Toktogul reservoir which generates hydropower demanded mainly in winter for heating. Downstream Uzbekistan and Kazakhstan need irrigation water in summer, primarily to grow an export crop (cotton). Regional agreements obliging Kyrgyzstan to higher summer discharges in exchange for fossil fuel transfers from downstream riparians in winter have been unsuccessful, due to lack of trust between the parties. Striving for self-sufficiency in irrigation water, Uzbekistan initiated new reservoir construction. This paper examines their economic impact. We report a laboratory experiment modelling the Syr Darya scenario as a multi-round, three-player trust game with non-binding contracts. Payoff schemes are estimated using real-life data. While basinwide efficiency maximisation requires regional cooperation, our results demonstrate that cooperation in the laboratory is hard to achieve. Uzbek reservoirs improve cooperation only weakly and their positive impact is limited to low-water years.